In the Hands of the People : Thomas Jefferson on Equality, Faith, Freedom, Compromise, and the Art of Citizenship - Jefferson, Thomas 1743-1826.; Meacham, Jon; Gordon-Reed, Annette; Ragosta, John A.; Thomas Jefferson Foundation (New York : Random House, 2020)
"Thomas Jefferson believed in the covenant between a government and its citizens, in both the governments responsibilities to its people and also the peoples responsibility to the republic. In this illuminating collection, a project of the Thomas Jefferson Foundation, #1 New York Times bestselling author Jon Meacham has gathered Jeffersons most powerful and provocative reflections on the subject, drawn from public speeches and documents as well as his private correspondence. Still relevant centuries later, Jeffersons words provide a manual for U.S. citizenship in the twenty-first century. His thoughts will re-shape and revitalize the way readers relate to concepts including Freedom: "Divided we stand, united we fall." The importance of a free press:"Were it left to me to decide whether we should have a government without newspapers, or newspapers without a government, I should not hesitate a moment to prefer the latter." Public education: "Enlighten the public generally, and tyranny and oppressions of body & mind will vanish like evil spirits at the dawn of day." Participation in government: A citizen should be "a participator in the government of affairs not merely at an election, one day in the year, but every day.""--
Keywords: Jefferson, Thomas, -- 1743-1826 -- Quotations; Jefferson, Thomas, -- 1743-1826 -- Political and social views; Citizenship -- United States; United States -- Politics and government; Philosophy; Quotations, maxims, etc